AMRITSAR 1919 : AN EMPIRE OF FEAR & THE MAKING OF A MASSACRE - Wagner, Kim A. (Yale University Press, 2019)
The Amritsar Massacre of 1919 was a seminal moment in the history of the British Empire, yet it remains poorly understood. In this dramatic account, Kim A. Wagner details the perspectives of ordinary people and argues that General Dyer's order to open fire at Jallianwalla Bagh was an act of fear. Situating the massacre within the "deep" context of British colonial mentality and the local dynamics of Indian nationalism, Wagner provides a genuinely nuanced approach to the bloody history of the British Empire.